Triphasic waves in electroencephalogram as a possible early marker of carcinomatous meningitis: a case report. Issue 33 (14th August 2020) - Liu, Chang; Cheng, Shihuan; Ma, Yue; Liu, Caiyun; Lv, Yudan
Abstract: Rationale: Carcinomatous meningitis is a rare neurological complication. This condition is difficult to diagnose, and misdiagnosis is common because the clinical manifestations are variable. Cerebrospinal fluid (CSF) cytology is the gold standard for diagnosis. Repeated lumbar puncture is required because of the low positive rate. Our case showed triphasic waves (TWs) in an electroencephalogram (EEG) before cancer cells were detected in cytology. We report this case to demonstrate that TWs in EEG may be a prognostic marker in patients with carcinomatous meningitis. Patient concerns: A 76-year-old Chinese male displayed incremental headache, nausea, emesis, and intermittent fever for 2 months. A routine scalp EEG showed mild slow background activity. The CSF analysis demonstrated a slight increase in protein, and the white blood cell count was in the normal range. Cytology did not show any atypical cells. Viral meningitis was considered for the first time. Diagnosis: After admission, a long-term EEG was performed because of his fever and mild abnormalities in the routine EEG. The second EEG showed asymmetric TWs in the frontal brain regions. Lung adenocarcinoma was found after systemic investigation. Finally, the patient was diagnosed with carcinomatous meningitis based on repeated CSF cytology. Interventions: The patient received systemic chemotherapy in the Department of Oncology. Outcomes: The patient was followed up monthly, and he was lost to follow-up in the sixth month after carcinomatous meningitis was diagnosed. Lessons: It is difficult to make a diagnosis in the early stage of carcinomatous meningitis because the clinical manifestations lack specificity. Repeated lumbar puncture is time consuming and is painful for the patients. In our case, TWs in EEG were detected before cancer cells were found in cytology. EEG should be performed when carcinomatous meningitis is under consideration.